Magnitude of work related injury, associated factors and its disparity across selected occupations in Ethiopia: Systematic review and meta-analysis - Wodaje Gietaneh; Muluye Molla; Muluneh Alene; Daniel Shitu (Elsevier, 2023)
Background: Globally, work related injury has been continued as a major public health problem. In Ethiopia there are few fragmented empirical studies particularly among workers of fast growing sectors and there is no a national representative study on work related injury. Therefore, this study aims to determine the magnitude of work related injury associated factors and its disparity among construction, textile and municipal solid waste management workers in Ethiopia. Objective: To determine magnitude of work related injury &associated factors and its disparity across selected occupations in Ethiopia Method: Both published and unpublished articles conducted in Ethiopia on work related injury were searched between the periods 12 October, 2019 to 15 December, 2019. Random effect model was employed to estimate the overall magnitude of occupational injury and its predictors. Results: The overall magnitude of work related injury was 39.35% (95% CI: 27.40, 51.30 %). Subgroup analysis revealed that there was slight disparity across occupations and regions. Drinking alcohol, smoking cigarette, khat chewing habit, work related stress, level of education and utilization of PPE were significantly associated with work related injury. Conclusion: This study found that more than 1 in 3 workers had at least one occupational injury at work. There was slight disparity across occupations and regions. It is strongly recommend that health education programs about the risk of substance use on occupational injury and apply strict occupational safety practices regulations should be strengthened.